An experimental study on the ontology of relations. - Orilia, Francesco; Paolini Paoletti, Michele (Synthese, 2024)
There is an ongoing debate on the ontology of relations, which features four main competing approaches: directionalism, positionalism, anti-positionalism, and primitivism. This paper focuses on a particular version of positionalism, namely role positionalism, and proposes the results of an experimental philosophy research concerning aspects of it. We tested the intuitions of ordinary subjects regarding the inter-relational generality of the roles typically assumed for spatial and kinematic relations, namely source, destination, theme, location. According to a 2014 paper by Orilia, this generality is rather wide, as it encompasses relations of temporal order, causation, quantitative order, transaction, possession, and parthood. Our findings do not support this proposal, except for parthood, and, in a limited way, for temporal order. We also tested the intuitions of ordinary subjects regarding the contrast between the pro-converses option, according to which non-symmetric relations split into distinct converse relations, and the anti-converses option, according to which non-symmetric relations have no distinct converses. Although traditionally positionalism is associated to the latter option, in recent works by Orilia role positionalism is associated to the former option for at least some relations, while remaining anchored to the latter option for other relations. Our findings support this mixed line to some extent, but not quite in the way suggested by Orilia in such works.